2022
DOI: 10.1021/jacs.1c11757
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Orbital Composition and Activity of LaMnxNi1–xO3 Nanostructures toward Oxygen Electrocatalysis

Abstract: The atomistic rationalization of the activity of transition metal oxides toward oxygen electrocatalysis is one of the most complex challenges in the field of electrochemical energy conversion. Transition metal oxides exhibit a wide range of structural and electronic properties, which are acutely dependent on composition and crystal structure. So far, identifying one or several properties of transition metal oxides as descriptors for oxygen electrocatalysis remains elusive. In this work, we performed a detailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 43 publications
0
26
1
1
Order By: Relevance
“…4), this trend suggests that increasing covalency of the Fe-O bond has a positive effect on the electron transfer dynamics to O 2 , removing surface V Fe which can act as a hole trapping site. 30,31 Finally, Fig. 9a and b display the effect of the La : Fe bulk ratio on the photoresponses associated with the hydrogen evolution reaction (HER) in Ar-purged 0.1 M Na 2 SO 4 electrolyte at pH 12 under the chopped illumination of 405 nm with a photon ux of 5.42 Â 10 19 m À2 s À1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4), this trend suggests that increasing covalency of the Fe-O bond has a positive effect on the electron transfer dynamics to O 2 , removing surface V Fe which can act as a hole trapping site. 30,31 Finally, Fig. 9a and b display the effect of the La : Fe bulk ratio on the photoresponses associated with the hydrogen evolution reaction (HER) in Ar-purged 0.1 M Na 2 SO 4 electrolyte at pH 12 under the chopped illumination of 405 nm with a photon ux of 5.42 Â 10 19 m À2 s À1 .…”
Section: Resultsmentioning
confidence: 99%
“…4), this trend suggests that increasing covalency of the Fe–O bond has a positive effect on the electron transfer dynamics to O 2 , removing surface V Fe which can act as a hole trapping site. 30,31…”
Section: Resultsmentioning
confidence: 99%
“…126,127 For example, Fermin et al conducted detailed experimental and theoretical computational studies on LaMn x Ni 1-x O 3 perovskite, establishing a correlation between the orbital composition and the corresponding OER activity. 128 Systematic electrochemical results showed that the OER activity of LaMn x Ni 1-x O 3 decreased with the increase of Mn content, which proved that the surface composition has a crucial function on the OER activity of LaMn x Ni 1-x O 3 . Zongping Shao et al reported a comparative study of the undoped SrCoO 3-δ (SCO) and the SrCO 1-y Si y O 3-δ with doping 5% Si (Si-SCO).…”
Section: Strategies For Performance Optimization Of Perovskite Catalystsmentioning
confidence: 88%
“…[122][123][124] Identification of the relevant redox couples is thus a natural choice for mechanistic discussions and has led to the recent insight that the OER is a first order reaction with respect to the Mn density of states, while the ORR is of second order. 125 Moreover, the Mn 3+/4+ redox couple is essential for the evolution of oxygen in natural photosynthesis as well as for electrodeposited Mn oxides 126 because Mn 4+ togetherwith Mn 3+ has been proposed as a necessity for the OER and because its midpoint potential is similar to that of the OER. The M 3+/4+ redox couple is likewise important for the OER on other transition metal oxides, 126 where the detection of M 4+ has been correlated with oxygen evolution for a Co oxide.…”
Section: Summary and Perspectivementioning
confidence: 99%